Corrigendum: "Design and operation of the ATLAS Transient Science Server" (2020, PASP, 132, 085002). (5th February 2021) - Smith, K. W.; Smartt, S. J.; Young, D. R.; Tonry, J. L.; Denneau, L.; Flewelling, H.; Heinze, A. N.; Weiland, H. J.; Stalder, B.; Rest, A.; Stubbs, C. W.; Anderson, J. P.; et al.
Abstract: In Smith et al. we published estimates of the volumetric rate of supernovae within 100 Mpc. These were incorrect and we present the correct values in this corrigendum.